An Assessment of the Effects of Hydrotherapy During the Active Phase of Labor on the Labor Process and Parenting Behavior. (March 2019) - Tuncay, Semra; Kaplan, Sena; Moraloglu Tekin, Ozlem
This study was conducted to assess the effect on labor process and parenting behavior of hydrotherapy applied during the active phase of labor. This quasi-experimental study was conducted by using an equivalent comparison group ( n = 40). The participants in the experimental group whose cervical dilation was 5 cm were taken to the hydrotherapy tub. This application continued until cervical dilation reached 10 cm. The Participants Questionnaire, The Birth Follow-up Questionnaire, The Postpartum ]collection tools. The duration of the active phase and second stage of labor was extremely short in the experimental group in comparison with the equivalent comparison group ( p = .001). The Visual Analogue Scale (VAS) scores of the experimental group were lower than those of the equivalent comparison group when cervical dilation was 6 cm and 10 cm ( p = .001). The experimental group also displayed more positive parenting behavior and positive labor feeling ( p = .001).